The Effectiveness of The Group Counseling Towards Motivation to Heal in Initiates in Drug Abuse Case - Nurul Aeni; Irfan Irfan; Fredy Akbar K (Faculty of Nursing, Universitas Hasanuddin, 2021)
Introduction: Drug convicts who do not receive rehabilitation tend to have low motivation to recover and stop drug abuse. Handling in an effort to increase the motivation of prisoners to recover from drug abuse is through the group counseling method. Group counseling provides encouragement and motivation to make changes in individuals. This type of research uses a one group pre-post test research design to compare the motivation recover before and after group counseling. Sampling in this study were prisoners of drug abuse cases, with a sample size of 20 people. Methods: The sampling technique was non-random sampling, namely purposive samling. The data was collected using a questionnaire, the result of statistical tests were carried out by the normality test, then the date were analyzed using the paired T test. The analysis result showed that the value of P=0.000 (P <0,05). Result: So it can be concluded that there is a diffrence in motivation recover before group counseling after group counseling is done. This means that there is an influence of group counseling on the motivation to recover in prisoners of drug abuse cases at the Class II B Rutan in Majene. Conclusions: It is hoped that the state prisoners will further improve the quality of services and coaching activities for inmates with drug abuse cases and can apply guidance knowledge and group counseling to increase motivation. To recover in prisoners of drug abuse cases.